Pengaruh Konsumsi Dalam Penggunaan Transaksi Non Tunai Terhadap Pertumbuhan Ekonomi di Indonesia - Fathia Naura Andini; Muhammad Husaini; Thomas Andrian; Arivina Ratih; Resha Moniyana; Neli Aida; Heru Wahyudi (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Cashless transactions are a practical way of buying and selling goods. Cashless transactions are used when people are carrying out consumption activities for goods and services. Cashless transactions are expected to affect economic growth in Indonesia. This study aims to determine the effect of cashless transactions on economic growth. The independent variables used in this study were the volume of debit card transactions, credit cards, e-money, and population growth. The dependent variable is GDP. Data obtained from Bank Indonesia and BPS. This study used the Ordinary Least Square (OLS) analysis method with Eviews 10. The results of this study show that the debit card variable has a positive significant effect, the credit card variable has a positive but not significant effect, the e-money variable has a positive but not significant effect, and the population growth variable has a significant but negative effect on economic growth in Indonesia.